Ma'afu's word is in the hills - What is a Noble's role in a democratised Tonga? - Brown Pulu, Teena (Te Kaharoa, 2012)
This paper explores the tensions played out between social groups in the Kingdom of Tonga and its overseas settlements, in relation to the democratisation of the homeland state.  Ethnographic detail pays attention to how the nobility – Tonga’s landed gentry – are responding to criticism that traditional leadership needs to politically reform.